Taxonomic review of Inella and Strobiligera (Gastropoda: Triphoridae) from Brazil - Fernandes, Maurício Romulo; Pimenta, Alexandre Dias (Zootaxa, 2019)
The triphorid genera Inella and Strobiligera are historically considered to represent one or two distinct groups, with recent studies claiming that Strobiligera comprises species with paucispiral or multispiral protoconchs, whereas only species with paucispiral protoconch occur in Inella. The present study aims to update the taxonomy of Inella and Strobiligera (with paucispiral protoconchs) from Brazil. Three main groups are recognized: Inella s.s. and Strobiligera show a simultaneous emergence of the three spiral cords of the teleoconch, the former possessing a discrete nucleus and the latter bearing a distinct globose protoconch; the “pseudo Inella” group has a late emergence of the median spiral cord of teleoconch. Four species were previously recorded from Brazil: I. unicornium, I. longissima, S. pompona and S. compsa, of which the three latter records are disregarded for being based on shells with broken apices and consequent uncertainty of identification. Twenty species in fact occur in Brazil: Inella s.s. is represented by I. apexbilirata and one possible new species; “pseudo Inella” includes “Inella” differens, “Inella” faberi, “Inella” galo sp. nov., “Inella” euconfio sp. nov., “Inella” leucocephala sp. nov., “Inella” faceta sp. nov., “Inella” maculata sp. nov., “Inella” vanilla sp. nov., and three possible new species; Strobiligera is represented by S. unicornium comb. nov., S. gaesona, S. dinea, Strobiligera campista sp. nov., Strobiligera santista sp. nov., and two possible new species. The “pseudo Inella” group is probably derived from unrelated lineages that converged to a simple type of paucispiral protoconch, requiring the examination of radular morphology to properly reallocate those species. The supposed restricted geographical range of triphorids with lecithotrophic development requires future investigations of the five species from the northwestern Atlantic/Caribbean that are herein recorded to Brazil. Key words: Triphoroidea, marine molluscs, lecithotrophic development, western Atlantic Introduction Triphoridae is a speciose family of marine snails that feed on sponges, with 642 Recent valid species (WoRMS 2018) and hundreds of undescribed species (Albano et al. 2011). The genus Inella Bayle, 1879 is one of the most challenging taxa in Triphoridae, especially because of its uncertain taxonomic limits and high number of described species (Marshall 1983). Inella and Strobiligera Dall, 1924 are historically considered to represent one or two distinct groups, with recent studies claiming that Strobiligera comprises species with paucispiral or multispiral protoconchs, whereas only species with paucispiral protoconchs occur in Inella (Fernandes & Pimenta 2014). A brief taxonomic overview of this issue will be addressed in the next lines. Hinds (1843) proposed the name Ino (preoccupied by the crustacean genus Ino Schrank, 1803; Inella Bayle is a replacement name) for cylindrical, elongated and acuminated triphorid shells. Jousseaume (1884) added that the shell of Inella is composed of at least 15 whorls, sculptured by spiral tubercles, with the last whorl presenting a depressed base and two apertures (i.e., the true aperture and the anterior canal). Laseron (1958) recognized that the Inella concept of Hinds (1843) mixed different shell types; however, Laseron broadened the definitions of Inella, as he also stated, warning that the use of protoconchs could need further generic revision. Kosuge (1966) defined Inella as having axial sculpture and three spiral cords on the teleoconch, a blunt and dome-shaped protoconch with a few spiral ridges, and suggested that Inella belongs to the most advanced group of triphorids. Marshall (1983) proposed the distinction between the “Triphora group” and the “Inella group” (composed of Inella Bayle and related genera) in Triphorinae, perhaps worthy of subfamily distinction, although this division is still informal (Marquet 1996). Marshall (1983: 19) also applied the term Inella s.l., recognizing that it contains “a number of natural groups that are worthy of genus-group status, most of which are as yet unnamed”. Simone (2006) interpreted Inella as triphorids with a very elongated shell, a relatively straight spire profile and a projected aperture. Rolán & Fernández-Garcés (2008) followed the concept of the catch-all taxon Inella s.l., uniting several species with very different shell forms under a more or less classical protoconch of Inella (i.e., without axial sculpture). Fernandes & Pimenta (2014) recognized that lecithotrophic species of Strobiligera have a very inflated protoconch (following Dall 1924), which is distinct from the reduced nucleus observed in Inella s.l., thus substantially reducing the number of species from the Atlantic Ocean previously allocated to the latter. Marshall (1983) did not indicate any junior synonym for Inella, but Rolán & Fernández-Garcés (2008) placed the type species of Strobiligera within Inella, which was later rejected by Fernandes & Pimenta (2014). Marquet (1996: 141) mentioned that “Marshall (1983) placed Norephora in synonymy with Inella”; this is not true, as Marshall (1983: 81) only indicated that “Norephora is probably closely related to Inella Bayle” when compared with Talophora Gründel, 1975. In fact, Fernandes & Pimenta (2014) suggested that Norephora is probably a synonym of Subulophora Laseron, 1958, pending further investigation. Wenz (1938 apud Kosuge 1966) suggested that Tristoma Menke, 1830 and Biforina Bucquoy, Dautzenberg & Dollfus, 1884 were synonyms of Inella, but Marshall (1983) stated that the first is a synonym of Triphora Blainville, 1828 and the second is a synonym of Monophorus Grillo, 1877. Although many species remain to be described in these genera, Inella and Strobiligera are represented altogether by 64 Recent species worldwide (Bouchet & Rosenberg 2013; Bouchet & Gofas 2014). Both genera are particularly common in mid-low depths of the continental shelf and in the continental slope, especially Strobiligera (Fernandes & Pimenta 2017a). Species with paucispiral protoconchs in both groups are absent from the eastern Atlantic (e.g., Bouchet 1985; Rolán 2005), although well-represented in the western Atlantic, with 27 Recent species (Simone 2006; Rolán & Fernández-Garcés 2008), mainly in the Caribbean and adjacent regions. Only four of these species were reported from Brazil: Inella unicornium Simone, 2006 is the only endemic species of this genus in Brazil; Strobiligera compsa (Dall, 1927) and Strobiligera pompona (Dall, 1927) were respectively considered misidentifications of Absalão (1989) and Rios (1975, 1985, 1994, 2009) by Fernandes & Pimenta (2014); and Inella longissima (Dall, 1881), reported by Rios (1985, 2009) from southern Brazil, replacing his prior identification of Inella triserialis Dall, 1881 (Rios 1975). The main objective of the present work is to update the taxonomy of Inella and Strobiligera species with paucispiral protoconchs, given that Strobiligera species from Brazil with multispiral protoconchs were already reviewed by Fernandes & Pimenta (2014), filling a large gap in taxonomic knowledge.